Uso de veículos elétricos em sistemas de transporte de cargas: avaliação dos benefícios em relação aos veículos movidos a óleo diesel - Lima, Douglas Leonardo de (2022)
The search for choices for the transport of goods that cause less impact on the environment and society has increased in academia and business in recent years. In fact, road freight transport is one of the sectors responsible for a large part of the goods transported in metropolises, in addition to making an important contribution to the emission of greenhouse gases. One of the alternatives to make this transport more efficient and sustainable is to reduce the use of fossil fuels. Current literature presents research on the economic, environmental, advantages and disadvantages of using electric vehicles in cargo transport systems in large urban centers. However, no studies were found that assess the environmental and economic impacts in relation to the use of electric vehicles in fractional load transport systems under the conditions presented in Brazil, and this aspect is considered a gap in this research. Thus, this dissertation aimed to evaluate the economic and environmental benefits of the use of electric vehicles used in fractional cargo transport systems in Brazil. The development of the research was in the form of two case studies carried out in the Metropolitan Region of São Paulo, through the acquisition of in loco data, of an electric truck and another diesel powered by simultaneously operating in one of the largest beverage distributors in Brazil. Thus, data relating to the use of the electric vehicle were compared to that of an equivalent diesel-powered vehicle, following similar schedules of scheduled deliveries. The results of the comparison carried out showed that the electric vehicle was more advantageous from the point of view of a more economical and environmentally more favorable operation. Therefore, this work contributed to the theory insofar as it carried out a comparison between an electric vehicle and a diesel one, a comparison that does not yet exist in the literature when it comes to Brazil. From a practical point of view and of contribution to society, the conclusions established here allow the identification of relevant reductions in costs and emission of greenhouse gases, with possibilities to generate a more sustainable logistical operation.